Performance prediction and techno-economic analysis of solar dish/stirling system for electricity generation. (5th January 2020) - Zayed, Mohamed E.; Zhao, Jun; Li, Wenjia; Elsheikh, Ammar H.; Zhao, Zhennan; Khalil, A.; Li, Hao
Highlights: A Solar Dish/Stirling (SDS) system was experimentally established and thermodynamically modeled. An analysis of the daily, monthly, and annual performances of the SDS system was performed. The SDS system produced 28.748 MWh annually, with a yearly overall efficiency of 19.55%. The levelized energy cost of the system estimated to be 0.2565 /kWh. Abstract: In this study, a new commercial Solar Dish/Stirling (SDS) system with a rated power of 25 kW is experimentally established and thermodynamically modeled. A mathematical model implemented in MATLAB software is developed to simulate the proposed SDS system operation in order to analyze its performance, under conditions of Tianjin, China. An analysis of the daily, monthly, and annual performances of the investigated SDS system is performed. In addition, a techno-economic viability for assessing the electricity cost and life cycle cost of the SDS system is also performed. The results indicated that the proposed SDS system produces 28.748 MWh annually, with a yearly net overall efficiency of 19.55%, and achieves maximum energy of 3.8 MWh with a monthly average efficiency of 22.75% in June. From the energy cost analysis, the levelized energy cost of the SDS system is estimated to be 1.719 CNY/kWh (0.2565 /kWh). In conclusion, the present study identifies the actual commercial and economic situation of the Dish Stirling technology in China, taking into account the China's feed-in tariff of CSP systems (1.2 CNY/kWh), and it also provides a new theoretical guidance for predicting the annual performance and evaluating the economic situation of the SDS systems.